The blue carpenter bees: a synopsis of the "Cyaneoderes group" of genus Xylocopa Latreille, 1802 (Hymenoptera: Apidae). (2nd April 2016) - Mawdsley, Jonathan R.
Abstract: A review is presented of the species included within the "Cyaneoderes group" of the genus Xylocopa Latreille, 1802, subgenus Koptortosoma Gribodo, 1894. The 14 names applied to members of this group by previous authors represent six valid species. Females of five species in this group have bright blue and black pubescence on the dorsal surface: X. abbotti (Cockerell, 1909); X. bangkaensis Friese, 1903; X. caerulea (Fabricius, 1804); X. insularis Smith, 1857; and X. tumida, Friese, 1903. A key, diagnostic table, and set of illustrations is presented to facilitate the identification of females of all five species. The known males of species in this group ( X. caerulea and X. insularis ) are illustrated. Xylocopa dormeyeri Enderlein, 1909, is placed as a synonym of X. insularis Smith, while X. meade-waldoi Hurd, 1959, is placed as a synonym of X. caerulea (Fabricius), New Synonymies. Diagnostic notes are presented for X. incompleta Ritsema, 1880, a species with bright orange (rather than blue) pubescence, which was included in the "Cyaneoderes group" by previous workers.